Entrepreneurs and Entrepreneurship in the Exposé of the Prime Ministers: From Tadeusz Mazowiecki to Mateusz Morawiecki - Kamosiński, Sławomir (Studia Historiae Oeconomicae, 2020)
The Prime Minister’s program speech, called the exposé, attracts particular attention. Its essence comes down to presenting the government’s program. In a few key words, the Prime Minister often summarizes the framework proposals of his government in terms of economic policy, social policy, education, health care, the army as well as individual social and professional groups. The words spoken by the Prime Minister, asking for confidence in the government that has just been formed set the direction for the entire Council of Ministers for subsequent years. In this regard, there is a need to examine the economic policy of every Prime Minister in office since 1989 considering entrepreneurs. What offer did the heads of government make to entrepreneurs, what kind of support could this group count on, how were the institutions supporting the economy and political institutions evaluated? The aim of this article is to find answers to the presented problems.